Is Mandibular Fossa Morphology and Articular Eminence Inclination Associated with Temporomandibular Dysfunction? - Paknahad, Maryam (J Dent (Shiraz), 2016)
STATEMENT OF THE PROBLEM: Finding a significant relationship between temporomandibular joint (TMJ) morphology and the incidence of temporomandibular dysfunction (TMD) may help early prediction and prevention of these problems. PURPOSE: The purpose of the present study was to determine the morphology of mandibular fossa and the articular eminence inclination in patients with TMD and in control group using cone beam computed tomography (CBCT). MATERIALS AND METHOD: The CBCT data of bilateral TMJs of 40 patients with TMD and 23 symptom-free cases were evaluated. The articular eminence inclination, as well as the glenoid fossa depth and width of the mandibular fossa were measured. The paired t-test was used to compare these values between two groups. RESULTS: The articular eminence inclination and glenoid fossa width and depth were significantly higher in patients with TMD than in the control group (p < 0.05). CONCLUSION: The articular eminence inclination was steeper in patients with TMD than in the control group. Glenoid fossa width and depth were higher in patients with TMD than that in the control group. This information may shed light on the relationship between TMJ morphology and the incidence of TMD.